O surgimento do português brasileiro: Mudanças linguísticas e mudanças tecnológicas no Brasil, séculos 18 e 19 - Elaine Chaves (2013)
Aiming to contribute to the interpretation of the actuation problem, we are seeking for the answers of two questions: Why changes occur in a given moment of time and not in another? And why in a given place and not in another? We identified a linguistic change when we analyzed the use of the prepositions [a] and [para] in verbal complements that can be clitized. We noticed that a linguistic change form started to be defined in the first half of the Nineteenth Century and it was (almost) completed in the first half of the Twentieth Century. Our samples were extracted from private letters, in addition to readers letters and news published in newspapers of Ouro Preto (Brazil). Thus, we documented a linguistic change, identifying an established place and moment. We propose that this established moment is linked to a fact that took place back then: in the 1840s there was in Ouro Preto a growing number of local newspapers and, concurrently, a diversification of their running and in the quantity of copywriters there. That way, by the periodic press, new agents started to spread their texts and their grammar, namely, their knowledge of their mother tongue. Thus, the manifestation of the new writers grammar was captured in the forms, which had a quantitative nature, proving the linguistic change mentioned above. Other samples were also used in this research: private letters, readers letters and news published in Lisbon in the same period of time. The analysis of the use of the prepositions [a] and [para] in verbal complements that can be clitized showed that the linguistic change that occurred in Ouro Preto did not occur in Lisbon. This fact enabled us to verify that the linguistic change analyzed by us occurred in a given place and not in another, which constitutes evidence that the historical contextualization had been, in fact, a relevant contribution. The dating of the change described here co-occurs to the dating of many other processes of change about Brazilian Portuguese (BP) already investigated. These investigations support the argument that BP and European Portuguese grammars are different.